Fabrication and testing of bioinspired composites with curved multilayer microstructures - Chan, Xin Ying (2023)
Natural strong and stiff composites exhibit complex microstructures that are responsible for their outstanding strength, stiffness and toughness. Although horizontal nacre-like microstructures have demonstrated great potential in synthetic composites, they demonstrate high performance along a specific loading direction only. Here, we study how complex curved multilayered microstructures made of aluminium oxide microplatelets in a soft polymeric matrix can possess a combination of both stiffness and toughness. To do so, magnetically assisted slip casting was used to direct the microplatelets into periodic orientations as reported in previous studies, while the porous substrate used for the slip casting was designed with a raised step of different heights to control the shape of the oriented layers. The samples’ microstructures achieved in-plane modulation of the microplatelet orientation and the mechanical properties under compression were enhanced compared to samples with layers parallel to the horizontal plane. The microstructured design proposed here could be used to make more resilient bioinspired composites.